Ni(OH)(2)@Ni core-shell nanochains as low-cost high-rate performance electrode for energy storage applications - Urso, Mario (Sci Rep, 2019)
Energy storage performances of Ni-based electrodes rely mainly on the peculiar nanomaterial design. In this work, a novel and low-cost approach to fabricate a promising core-shell battery-like electrode is presented. Ni(OH)(2)@Ni core-shell nanochains were obtained by an electrochemical oxidation of a 3D nanoporous Ni film grown by chemical bath deposition and thermal annealing. This innovative nanostructure demonstrated remarkable charge storage ability in terms of capacity (237 mAh g(−1) at 1 A g(−1)) and rate capability (76% at 16 A g(−1), 32% at 64 A g(−1)). The relationships between electrochemical properties and core-shell architecture were investigated and modelled. The high-conductivity Ni core provides low electrode resistance and excellent electron transport from Ni(OH)(2) shell to the current collector, resulting in improved capacity and rate capability. The reported preparation method and unique electrochemical behaviour of Ni(OH)(2)@Ni core-shell nanochains show potential in many field, including hybrid supercapacitors, batteries, electrochemical (bio)sensing, gas sensing and photocatalysis.